The unbearable lightness of being a designer in Cyprus - Panayides, Angelos (My University, 2011)
The evolving role of a designer in the local creative industry and the creative frontiers is the topic that I would like to discuss. As the 5th United Designs becomes a turning point for the arts and culture in Cyprus, the fact itself generates questions concerning the opportunities, threads, ambitions and generally the artistic landscape of the island, where a designer lives and works. The nature of the economy and businesses in our small, divided island defines and imposes silently the possibilities a designer should have during a lifelong career. Conveying ideas, concepts or perhaps interpreting the world around us is limited by shorter deadlines, smaller budgets and admittedly less design-educated customers. The graphic design field is tightly tied upon commercial terms as professional practitioners are trying to make a living. Additionally the omnipresent consequences of financial crisis still reverberate in our corridors. Can negative times be translated as an opportunity to escape from dull and decedent projects or will the existing creative limits of a designer come closer than ever?
Keywords: Graphic design; Visual culture